Management of expenditures of retail trade companies by responsibility centers Управление расходами предприятий розничной торговли по центрам ответственности - Milash Inna V.; Garkusha Natalya N. (Problemi Ekonomiki, 2011)
The article studies and summarizes theoretical concepts of the «responsibility centre». Expenditure management system is recommended for retailers by responsibility centers. В статье исследованы и обобщены теоретические положения понятия «центр ответственности». Рекомендована система управления расходами предприятий розничной торговли по центрам ответственности.